Strategi Pengembangan UMKM Games in Your Area melalui Optimalisasi Digital Marketing - Shevia, Shevia; Christiarini, Renny (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the era of the fourth industrial revolution in Indonesia, it is crucial for Micro, Small, and Medium Enterprises (MSMEs) to continuously update themselves to survive in the midst of intense competition. This study explores a development strategy for the MSME "Games in Your Area" through the optimization of digital marketing. This Community Service is implemented through three stages: survey, implementation, and evaluation. The objective of this Community Service is to enhance the number of customers, social media engagement, and product sales at Games in Your Area. Implementation involves optimizing Instagram and increasing the number of reviews on Google Review. The results indicate a significant improvement, with a 50% increase in the number of customers, a 20% rise in Game Rate sales, and an 80% increase in Game Rental sales. Thus, the digital marketing strategy proves effective in enhancing the performance and engagement between consumers and the MSME â€œGames in Your Areaâ€